Cross-country differences in return and volatility metrics of world equity indices - Iskandar Sheraliev; Robert Ślepaczuk (Central European Economic Journal (CEEJ), 2023)
This research seeks to determine whether the cross-country differences in return and volatility metrics in various country equity indices can be explained by differences in economic development. We base the study on the MSCI IMI net income indices on two samples: a 51-country sample from the period 31 May 2002 to 28 February 2022, and a 75-country sample from the period 30 November 2010 to 28 February 2022. In this study, countries are grouped into four categories: frontier, emerging, early-developed, and developed, based on gross domestic product (GDP) per capita. The Kruskal-Wallis rank sum test is used to find cross-group differences, and the results are further analyzed with the pairwise Wilcoxon rank sum test with the Holm-Bonferroni p value adjustment method. The results are relatively unintuitive and show that there is no significant cross-group difference in daily and monthly returns. There is evidence of a considerable difference in volatility metrics, especially in the case of the emerging market group, which is significantly different from the three other groups. The results are slightly sensitive to time period change and very sensitive to changes in income categories of some countries.
Keywords: 330; Frontier markets; Emerging markets; Developed markets; Cross-country differences; Volatility; GDP per capita